Disassembly and characterization of liquid crystal screens. Issue 6 (June 2013) - Juchneski, Nichele CF; Scherer, Janine; Grochau, Inês H; Veit, Hugo M
The technology used in the manufacturing of televisions and monitors has been changing in recent years. Monitors with liquid crystal displays (LCD) emerged in the market with the aim of replacing cathode ray tube monitors. As a result, the disposal of this type of product, which is already very high, will increase. Thus, without accurate knowledge of the components and materials present in an LCD monitor, the recycling of materials, such as mercury, thermoplastic polymers, glasses, metals and precious metals amongst others, is not only performed, but allows contamination of soil, water and air with the liberation of toxic compounds present in this type of waste when disposed of improperly. Therefore, the objective of this study was to disassemble and characterize the materials in this type of waste, identify the composition, amount and form to enable, in further work, the development of recycling routes. After various tests and analyses, it was observed that an LCD display can be recycled, provided that precautions are taken. Levels of lead, fluoride and copper are above those permitted by the Brazilian law, characterizing this residue as having a high pollution potential. The materials present in printed circuit boards (base and precious metals)—thermoplastics, such as polyethylene terephthalate, acrylic, acrylonitrile butadiene styrene and polycarbonate and metals, such as steel and aluminum, and a layer of indium (in the internal face of the glass)—are components that make a point in terms of their potential for recycling.